Cross-Cultural Philosophy of Religion: Case Study of Mekar Mukti and Sertajaya - Andreas Yumarma (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Mekar Mukti and Sertajaya are the villages in Jababeka city which are coloured by the fast development of industrial companies, residences, expatriate immigrants and new comers from different areas of Indonesia. People in here live together with those who have different cultures and religions. Encounter of the different followers of religions with their various cultural background has an impact of a gradual process of awareness towards cross-cultural faith in these villages. However political influence and local leaders use religious elements to influence the vote and to get power. Religiousity and its expressions, human limitedness to the mystery of the Divine, and the conception of human life in the world as a temporary journey to God provide seeds which are necessary for the possibilities of cultural faith in religion, mutual respect, inclusiveness spirit and cooperation among the followers of religions. This writing, therefore, is intended to give an inspiration on how to minimise social, religious and economic gaps from the perspetive of cross-cultural faith. Hopefully it also becomes means that are necessary to create harmony, respect, tolerance, and inclusiveness spirit among citizens of Mekar Mukti and Sertajaya and Indonesia in general. Keywords: Mekar Mukti and Sertajaya, encounter of the different followers of religions, cross-cultural faith, religiousity, human limitedness, mystery of the Divine, temporary jorney to God.